KAJIAN PENERAPAN RETRIBUSI TERMINAL LANDUNGSARI DITENGAH PANDEMI COVID-19 TERHADAP PENDAPATAN SOPIR ANGKOT - Poppy Indri Hastuti; Sri Indah (BADAN PENERBITAN UNIVERSITAS WIDYAGAMA, 2020)
ABSTRACTThe terminal is a place for stopping public transportation, both city and intercity, where potential passengers meet. with an angkot that takes him to his destination. People tend to choose urban and inter-city transportation as a means of transportation to the target area. To review retribution at the Landungsari terminal in Malang City as a service to use a parking space for transportation vehicles while waiting for departure, amidst the Corona Covid-19 virus epidemic. The fact is that public transportation drivers accept the application of terminal fees imposed by the Malang City government, the stipulation is Rp. 1,000 (one thousand rupiah). During the Corona Covid-19 Pandemic, the activities of the drivers were disturbed so that the income level decreased due to the absence of passengers. The government implements terminal fees in order to expect remuneration for the location of the terminal provided by the government for the community, especially public transportation drivers looking for income. It is recommended for drivers to comply with tax retribution payments in a timely manner so that they can help and participate in increasing regional tax results in the city of Malang in the midst of the Corona Covid-19 pandemic, by following the health protocols of both drivers and public transportation passengers such as washing hands, wearing masks and maintaining distance. Keywords: Public transportaition, corona, retribution, stationABSTRAKTerminal merupakan tempat pemberhentian kendaraan umum, baik kota maupun antarkota, tempat calon penumpang bertemu. dengan angkot yang membawanya ke tempat tujuannya. Masyarakat cenderung memilih transportasi perkotaan dan antar kota sebagai alat transportasi menuju daerah sasaran. Meninjau retribusi di terminal Landungsari Kota Malang sebagai pelayanan penggunaan tempat parkir kendaraan angkut sambil menunggu pemberangkatan, di tengah wabah virus Corona Covid-19. Faktanya, para sopir angkot menerima pemberlakuan retribusi terminal yang diberlakukan oleh Pemerintah Kota Malang, ketentuannya Rp. 1.000 (seribu rupiah). Pada saat Pandemi Corona Covid-19, aktivitas para pengemudi terganggu sehingga tingkat pendapatan menurun akibat tidak adanya penumpang. Pemerintah menerapkan biaya terminal dengan harapan adanya remunerasi bagi lokasi terminal yang disediakan oleh pemerintah bagi masyarakat, khususnya para pengemudi angkot yang sedang mencari penghasilan. Disarankan bagi para pengemudi untuk mematuhi pembayaran retribusi pajak secara tepat waktu sehingga dapat membantu dan berpartisipasi dalam meningkatkan hasil pajak daerah di kota Malang di tengah pandemi Corona Covid-19, dengan mengikuti protokol kesehatan keduanya. pengemudi dan penumpang angkot seperti mencuci tangan, memakai masker dan menjaga jarak. Kata kunci: Angkutan umum, korona, retribusi, stasiun